Engineering a Twenty-First Century Reading Comprehension Assessment System Utilizing Scenario-Based Assessment Techniques. Issue 1 (2nd January 2020) - Sabatini, John; O'Reilly, Tenaha; Weeks, Jonathan; Wang, Zuowei
Abstract : The construct of reading comprehension has changed significantly in the twenty-first century; however, some test designs have not evolved sufficiently to capture these changes. Specifically, the nature of literacy sources and skills required has changed (wrought primarily by widespread use of digital technologies). Modern theories of comprehension and discourse processes have been developed to accommodate these changes, and the learning sciences have followed suit. These influences have significant implications for how we think about the development of comprehension proficiency across grades. In this paper, we describe a theoretically driven, developmentally sensitive assessment system based on a scenario-based assessment paradigm, and present evidence for its feasibility and psychometric soundness.